2016
DOI: 10.5007/1980-0037.2016v18n5p557
|View full text |Cite
|
Sign up to set email alerts
|

Obesidade em adolescentes do Sul do Brasil: associação com fatores sociodemográficos, estilo de vida e estágio maturacional

Abstract: DOI: http://dx.doi.org/10.5007/1980-0037.2016v18n5p557 Excess body fat is associated with chronic degenerative diseases, being a global public health problem. The aim of this study was to investigate the association of obesity with sociodemographic factors, lifestyle (physical activity, dietary habits) and sexual maturation in high school students of a city in southern Brazil. This is a crosssectional study with 820 adolescents enrolled in public high schools of São José, Santa Catarina, Brazil, aged 14-17 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Guthold, Stevens, Riley and Bull [1] also indicated that Australia had the highest prevalence of physical inactivity among adolescents-precisely 89%-followed by New Zealand in the category of high-income Western Countries. Given the fact that regular physical activity and the practice of healthy diets are critical to shedding excess weight or maintaining a healthy weight, with a range of other health benefits [23], it is important to investigate better means of addressing the obesity epidemic among Australian adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Guthold, Stevens, Riley and Bull [1] also indicated that Australia had the highest prevalence of physical inactivity among adolescents-precisely 89%-followed by New Zealand in the category of high-income Western Countries. Given the fact that regular physical activity and the practice of healthy diets are critical to shedding excess weight or maintaining a healthy weight, with a range of other health benefits [23], it is important to investigate better means of addressing the obesity epidemic among Australian adolescents.…”
Section: Introductionmentioning
confidence: 99%